Does bat response to traffic noise support the misleading cue hypothesis?. (27th September 2019) - Geipel, Inga; Amin, Bawan; Page, Rachel A; Halfwerk, Wouter
Abstract: The world has become a noisier place due to the increase in urbanization. Noise is generally considered an impediment, altering an animal's behavior through masking or distraction. But noise can also provide useful information about the environment. For animals that rely on natural environmental noise as an indicator of favorable foraging conditions, increasing levels of anthropogenic noise might mislead informed decision-making. Bats use rain noise, a natural environmental cue, to delay their emergence from the roost, presumably to avoid sensory and metabolic costs associated with foraging in heavy rain. Here we tested the "misleading cue hypothesis, " asking whether traffic noise is mistaken for rain noise by bats. Given the acoustic similarity between rain noise and traffic noise, we predicted that bats would confuse the two. We conducted a playback experiment using rain, traffic, and ambient noise at natural roosts of common big-eared bats ( Micronycteris microtis, Phyllostomidae) and recorded bat emergence behavior. In contrast to their response to rain noise, the bats did not delay roost emergence in response to traffic noise. Thus, we found that bats were able to discriminate between traffic noise and rain noise and were not misled by similarity in acoustic parameters in the two noise types, when emerging from their roost. Emerging bats did show more exploration flights during traffic noise than during rain noise, but not during ambient noise, suggesting that they perceive traffic noise as a novel acoustic cue. Our data provide new insights into perception of traffic noise by bats. Abstract : With increased anthropogenic activity, the environmental cues animals use as indicators of favorable foraging conditions can become misleading. Bats delay their roost emergence during natural rain noise minimizing foraging in adverse environmental conditions. We asked whether acoustically similar traffic noise is a misleading cue, causing bats to delay hunting unnecessarily. Playback experiments show that bats can discriminate between natural rain noise and novel, artificial traffic noise, and thus are not deceived by this potentially misleading cue.